Age-Associated B Cell and T Helper Cell Dysfunction in Rhesus Macaques - (:unkn) unknown (My University, 2016)
The immune system undergoes drastic changes as we age, known as immunosenescence. An example of this is the dysfunction and subpopulation distribution changes of immune cells. Due to immunosenescence, the elderly have a higher risk of complications and rapid progression of new challenges to the immune system, including human immunodeficiency virus (HIV). In an effort to determine the mechanism of dysfunction of humoral immunity due to age, I compared B cell and T cell responses to non-specific, mitogenic stimuli between aged and young adult rhesus macaque peripheral blood mononuclear cells (PBMCs). Analysis by flow cytometry revealed several differences in B cell population distributions, activation, and signaling that could begin to explain the mechanism of immunosenescence in the elderly. CD4+ T helper cells help activate B cells and CD4-CD8- (double negative) T cells have a role in autoimmune diseases, which are more common in the elderly. Differences in CD4+ and CD4-CD8- T cell subpopulation distributions and CD28 expression with advanced age were also found, along with decreases in multifunctional T cells.
Keywords: Activation; B Cell; HIV; Immunosenescence; SIV; T Cell